Correlation between increased total serum IgE levels and clinical features in alopecia areata patients - Yijie Sun; Shuang Xu; Yujing Zhang; Yuxin Wang; Jianzhong Zhang; Xiangqian Li; Cheng Zhou (Frontiers in Immunology)
BackgroundsAlopecia areata (AA) is primarily associated with a Type 1 (Th1) inflammatory response, but emerging evidence also suggests a potential contribution of Type 2 (Th2) immunity. However, the relationship between IgE levels and pathogenesis of AA, as well as its clinical features, remains unclear, with limited and conflicting evidence in current research. This study aims to compare the total serum IgE levels between AA patients without atopic diseases and healthy controls, and to examine the correlation of IgE levels with gender, age, disease severity, disease duration, and affection of eyebrows, eyelashes, and nails.MethodsAA patients without other hair loss diseases and conditions, or systemic treatment known to affect serum IgE were included. Medical records of 436 patients and 181 normal controls were retrospectively analyzed between May 2018 and November 2024. Among AA patients, clinical features and total serum IgE levels were analyzed.ResultsThe elevated total serum IgE rate was observed in 31.0% of AA patients, which was significantly higher than that in control groups (P < 0.001). Among AA patients, total serum IgE levels differed significantly by gender (P = 0.002), age (P < 0.001), and disease severity (P = 0.040). Patients with alopecia universalis or totalis (AU/AT) had higher total serum IgE levels compared to those with localized AA (P = 0.049). No significant correlation was found between total serum IgE levels and disease duration.ConclusionsOur research reveal that total serum IgE levels are elevated in AA patients compared to control group. Male patients, children, and individuals with moderate-severe AA patients showed significantly higher IgE levels. These results suggest the involvement of IgE and Th2 cytokines in AA pathogenesis.